Assessing the Sustainability of Small Farmer Natural Resource Management Systems. A Critical Analysis of the MESMIS Program (1995-2010) - Astier, Marta; García-Barrios, Luis; Galván-Miyoshi, Yankuic; González-Esquivel, Carlos E.; Masera, Omar R. (Ecology and society, 2012)
Sustainability assessment oriented to improve current systems and practices is urgently needed, particularly in the context of small farmer natural resource management systems (NRMS). Unfortunately, social-ecological systems (SES) theory, sustainability evaluation frameworks, and assessment methods are still foreign not only to farmers but to many researchers, students, NGOs, policy makers/operators, and other interested groups. In this paper we examine the main achievements and challenges of the MESMIS Program (Spanish acronym for Indicator-based Sustainability Assessment Framework), a 15-year ongoing effort with impact in 60 case studies and 20 undergraduate and graduate programs mainly in Ibero-America that is attempting to cope with the stated challenges. The MESMIS experience shows that it is possible to conduct sustainability assessments in the context of small farmers through a long-term, participatory, interdisciplinary, and multi-institutional approach that integrates a solid theoretical background, a field-tested operational framework, learning tools specifically devised to facilitate the understanding of sustainability as a multidimensional and dynamic concept, and a growing set of case studies to apply to and get feedback from users. Specifically, through the dissemination of the MESMIS assessment framework in a large set of case studies in a contrasting set of social-ecological contexts, we have been able to: (a) characterize the NRMS, their subsystems, and their main interactions; (b) link attributes, i.e., general systemic properties, with sustainability indicators to assess critical socioeconomic and environmental aspects of the NRMS; (c) integrate indicators through multicriteria tools and to expose the multidimensional aspects of sustainability; (d) propose an initial multiscale assessment to articulate processes and actors at different spatial scales; (e) develop multimedia learning tools, i.e., Interactive-MESMIS, to help users understand dynamic concepts, trade-offs, and counter-intuitive behavior; and (f) promote participatory processes through role-playing games and agent-based simulation models. Key challenges are related to the need to conduct long-term longitudinal studies that fully capture system dynamic properties while at the same time actively involving relevant stakeholders through creative and lasting participative processes. We outline an improved assessment framework that should help move the program in this direction.